2000
DOI: 10.12968/ijpn.2000.6.7.9070
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric palliative care: a lack of research-based evidence

Abstract: Providing the best possible care for the child and family is paramount to health professionals working in paediatric palliative care. However, there is little research which enables practitioners to question their current practice. There are concerns about conducting research on children receiving palliative care at such a sensitive time for the child and his/her family. These concerns must be considered against the growing demand for clear standards and guidelines for practice within health care. According to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…7,8 Key ethical concerns include people's capacity to consent, particularly due to their frailty and changes in their cognitive functioning 9,10 ; maintaining dignity, safety, and well-being 11,12 ; and the burden on participants, especially children and the elderly. 13,14 Relying on family members' accounts to conduct retrospective research on end-of-life experiences is a valid approach, which can overcome these barriers. 3,[15][16][17] Family members' interpretations of the patient's dying experience can provide valuable information to improve service delivery and aid decision making about what could work better.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Key ethical concerns include people's capacity to consent, particularly due to their frailty and changes in their cognitive functioning 9,10 ; maintaining dignity, safety, and well-being 11,12 ; and the burden on participants, especially children and the elderly. 13,14 Relying on family members' accounts to conduct retrospective research on end-of-life experiences is a valid approach, which can overcome these barriers. 3,[15][16][17] Family members' interpretations of the patient's dying experience can provide valuable information to improve service delivery and aid decision making about what could work better.…”
Section: Introductionmentioning
confidence: 99%
“…107 This study found no systematic reviews and meta-analyses targeting pediatric population, which might be attributed to lesser reporting rates of pediatric palliative care among the palliative care journals 19 and a lack of researchbased evidence. 108 Focus on general palliative care 109 was relatively lesser compared to cancer, which again needs attention. This review found more articles on cancer which was evident since cancer was highly represented in medical journals per se.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst research in this new and rapidly evolving speciality has increased steadily over recent years, published outcome data to provide an evidence base on which care can be based is not adequate, [1][2][3][4][5] thus demonstrating the need for a clear research agenda to address key questions. Indeed criticisms have been levied that children's palliative care lacks a rigorous empirical basis 1 and that practice has developed through clinical experience, anecdotal evidence and modifications of adult palliative care management, 6 creating an opportunity to move services forward by identifying and pursuing key research topics.…”
Section: Introductionmentioning
confidence: 99%